2009
DOI: 10.1186/1478-4505-7-8
|View full text |Cite
|
Sign up to set email alerts
|

Research collaboration in Tehran University of Medical Sciences: two decades after integration

Abstract: Background: In 1985 medical schools were integrated into the Ministry of Health, and the Ministry of Health and Medical Education was created in Iran. Under this infrastructure education, research and service provision are unified, and it is expected that collaboration between researchers and decision makers become easier in such an integrated context. The question here is how the researchers behavior in the biggest medical university of the country towards collaboration is, i.e. how much do decision makers pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Previous studies indicated that only 3–6% of funding for research in the East Mediterranean region countries, including Iran, has come from non-governmental or private sectors [ 10 ]. This figure amounted to around 6% in the Tehran University of Medical Sciences (TUMS), which is the biggest medical university in Iran [ 11 ]. These findings suggest that the government is the main source of financial support for research in medical universities in Iran.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies indicated that only 3–6% of funding for research in the East Mediterranean region countries, including Iran, has come from non-governmental or private sectors [ 10 ]. This figure amounted to around 6% in the Tehran University of Medical Sciences (TUMS), which is the biggest medical university in Iran [ 11 ]. These findings suggest that the government is the main source of financial support for research in medical universities in Iran.…”
Section: Introductionmentioning
confidence: 99%
“…The absence of collaboration will affect co-operation in research. This issue was scrutinized in a quantitative study performed in the biggest medical university in Iran, with the findings demonstrating that the level of collaboration was not desirable (Majdzadeh et al 2009b).…”
mentioning
confidence: 99%
“…Almost half the project results had been used by the researcher (themselves) or other researchers to define future projects. This rate was 32% in another study conducted in Iran [ 26 ], whereas in studies conducted in other countries it was reported at 23%, 44.9% and 65% [ 9 , 12 , 13 ]. This shows that half of the studies are not related to their subsequent studies, a point worth reflecting upon.…”
Section: Discussionmentioning
confidence: 91%
“…Moreover, a specific organization, policymaker, manager, and/or the industry have ordered 10.24% of the studies. Other studies in Iran have estimated this figure at 11.8% [ 25 ] and 16% [ 26 ]. This figure is similar to that of securing research grants from other organizations.…”
Section: Discussionmentioning
confidence: 98%